Effect of dissolved oxygen and temperature on fatigue crack growth rate behaviour of SA312 Type 304L(N) material in water environment. (February 2017) - Arora, Punit; Singh, P.K.; Bhasin, V.; Rama Rao, A.
Highlights: Fatigue crack growth rate tests conducted in water at room temperature and 300 °C on SS 304L(N) material. The dissolved oxygen levels in water were varied from 10 ppb to 1500 ppb. Higher fatigue crack growth rate in water at room temperature under 0.005 Hz is primarily due to deformation induced martensite. Higher fatigue crack growth rate in water at 300 °C is due to corrosion-fatigue synergistic damage. Abstract: The present study aims at quantification of Fatigue Crack Growth Rate (FCGR) parameters under different dissolved oxygen levels in water at room temperature (RT) and 300 °C for SA312 Type 304L(N). The tests were conducted under 0.005 Hz loading frequency. With a presumption that strain rate (or frequency) does not affect FCGR in air at RT, a reference test was carried out in air under 10 Hz frequency for comparison purpose. The FCGR in water (0.005 Hz) is significantly higher than air reference test (10 Hz). The microscopic investigations revealed corrosion-fatigue synergy to be leading factor for higher FCGR in water at 300 °C. However, strain rate dependent Deformation-Induced-Martensite (DIM) transformation was predominant in water at RT. Recent studies on this material also brought out higher DIM formation under 0.01 Hz compared to 10 Hz at RT in air environment. The FCGR results in air environment are consistent with that in water at RT under lower frequency regime.